Hubungan Antara Ilmu Sosial Dan IPS (Sumber Dan Materi IPS) - Maudyla Ali Saragih; Nursakinah Lubis; Fatimah Zahara; Desmidar Harahap; Awaliah Syahidah Bintang; Eka Yusnaldi (Journal on Education, 2024)
Social Science and Social Studies are two interrelated disciplines that have an important role in shaping people's understanding of social, cultural, economic and political dynamics. The method we use in this research is literature study. The technique we use in analyzing data is qualitative analysis. Qualitative research is Qualitative analysis is used for non-numerical data that is textual or narrative in nature. Although often considered similar, they have fundamental differences in approach and objectives to be achieved. Social Science, as an academic field of study, aims to understand and analyze social phenomena through rigorous theoretical and methodological approaches. Meanwhile, Social Studies is a subject taught in schools with the aim of providing students with practical insights and basic knowledge about various aspects of social life. In this article, the topic of discussion is the source or material of Social Science, the relationship between social science and Social Science and also how society is used as a source of Social Science.